Geopolitics of Portugal in Atlantic Sea - Maulana Reza Adhitama (IPTEK Journal of Proceedings Series, 2019)
Neo-realism argues that states belong to an anarchic world in which there is no great power governing on it. State is required to have survival capability in a self-help system. Inter-state relations may encourage a country to exercise their power as a means of survival in an anarchist world. The Atlantic Sea plays a vital role in maintaining international stability and security to balance the power distribution within the region. Since days of discovery, Portugal have shown their capabilities in navigating the sea, through high seas, islands and across continents in looking for most-wanted sources at the time, spices. They have cemented their dominance at various strategic points along international shipping lanes. Further, having the longest coastline in Europe makes Portugal´s politics in maritime realm quite decisive. Based on the neo-realism perspective developed by Kenneth Waltz, the author outlines the strategic steps adopted by Portuguese towards transition of global power during post World-War II. This article reveals that construction of Portuguese national identity determines their national interest in regards of their foreign policy in maritime security policy.